Salicylic Acid Is Involved in Rootstock–Scion Communication in Improving the Chilling Tolerance of Grafted Cucumber - Fu, Xin; Feng, Yi-Qing; Zhang, Xiao-Wei; Zhang, Yan-Yan; Bi, Huan-Gai; Ai, Xi-Zhen (Frontiers in Plant Science, 2021)
Salicylic acid (SA) has been proven to be a multifunctional signaling molecule that participates in the response of plants to abiotic stresses. In this study, we used cold-sensitive cucumber and cold-tolerant pumpkin as experimental materials to examine the roles of SA in root–shoot communication responses to aerial or/and root-zone chilling stress in own-root and hetero-root grafted cucumber and pumpkin plants. The results showed that pumpkin (Cm) rootstock enhanced the chilling tolerance of grafted cucumber, as evidenced by the observed lower levels of electrolyte leakage (EL), malondialdehyde (MDA), and higher photosynthetic rate (Pn) and gene expression of Rubisco activase (RCA). However, cucumber (Cs) rootstock decreased the chilling tolerance of grafted pumpkins. Cs/Cm plants showed an increase in the mRNA expression of C-repeat-binding factor (CBF1), an inducer of CBF expression (ICE1), and cold-responsive (COR47) genes and CBF1 protein levels in leaves under 5/25 and 5/5°C stresses, or in roots under 25/5 and 5/5°C stresses, respectively, compared with the Cs/Cs. Chilling stress increased the endogenous SA content and the activity of phenylalanine ammonia-lyase (PAL), and the increase in SA content and activity of PAL in Cs/Cm plants was much higher than in Cs/Cs plants. Transcription profiling analysis revealed the key genes of SA biosynthesis, PAL, ICS, and SABP2 were upregulated, while SAMT, the key gene of SA degradation, was downregulated in Cs/Cm leaves, compared with Cs/Cs leaves under chilling stress. The accumulation of SA in the Cs/Cm leaves was mainly attributed to an increase in SA biosynthesis in leaves and that in transport from roots under aerial and root-zone chilling stress, respectively. In addition, exogenous SA significantly upregulated the expression level of cold-responsive (COR) genes, enhanced actual photochemical efficiency (ΦPSII), maximum photochemical efficiency (Fv/Fm), and Pn, while decreased EL, MDA, and CI in grafted cucumber. These results suggest that SA is involved in rootstock–scion communication and grafting-induced chilling tolerance by upregulating the expression of COR genes in cucumber plants under chilling stress.